Whither human IVF? Fertilisable oocytes selected on the basis of follicular temperature - Hunter, Ronald H. F. (J Assist Reprod Genet, 2018)
Bearing in mind specific parallels between cow and human ovarian physiology, as noted in the manuscript, we have measured whether the temperature in a pre-ovulatory follicle is cooler than that in adjacent tissues. Using a novel approach not requiring anaesthetics or surgical procedures, we found that follicular fluid bathing cow oocytes shortly before ovulation is cooler than the neighbouring uterine surface and cooler than deep rectal temperature (the reference body temperature in cattle). By contrast, Graafian follicles of comparable size and ultrasonic image that do not subsequently ovulate do not have a reduced antral temperature. Human pre-ovulatory follicles have previously been reported to be cooler than other ovarian tissues, so the divergence between ovulatory and non-ovulatory follicle temperature suggests a valuable addition to selection procedures currently used in human in vitro fertilisation (IVF) clinics. In future, oocytes to be subjected to IVF might best be those taken from cooler follicles. Follicular antral temperature could become a more sensitive indicator of oocyte potential that a purely morphological assessment.